The Prevalence of Musculosskeletal Sport Injuries Inprofessional Basketball Playeres - NEJAT, SEYEDFATEME (Journal of Clinical Physiotherapy Research, 2020)
Basketball is one of the most popular sport activities in the world and also has a high risk of sports injuries. For applying effective interventions for treatment and prevention of musculoskeletal injuries, reliable and accurate information about injury prevalence is essential. This study was performed with the purpose of evaluating of prevalence of musculoskeletal injuries in basketball players. In this descriptive observational study 36 athletes were participated. All data collected through standardized report and comprehensive evaluation was done for injury diagnosis. Data was collected with excel 2007 and analyzed with SPSS version 16. Ankle injury was recorded as the most common injury which 19 players (52.8% of players) experienced. Knee injury was the second common injury which 15 players suffered from.